Hazardous wastewater treatment by low‐cost sorbent with in situ regeneration using hybrid solar energy‐electrochemical system. (16th March 2021) - Khan, Muhammad Masood; Asghar, Hafiz Muhammad Anwar; Saulat, Hammad; Chawla, Muhammad; Rafiq, Sikander; Khan, Muhammad Mahmood; Ya Jie, Wang; Aslam, Muhammad; Mukhtar, Ahmad
Abstract: Hazardous industrial wastes negatively impact the environment by creating issues for aquatic as well as human's life. This study investigates the treatment of hazardous industrial wastewater using cost‐effective graphite adsorbent along with electrochemical regeneration integrated with renewable solar energy. The synthetic industrial effluent containing crystal violet dye was treated using an adsorbent (Nyex™ 1000) having a surface area of 1.0 m 2  g −1 . The efficiency of removing solute was found to be more than 90%. The adsorbent regeneration efficiency was achieved at 99.5% by passing a charge of 100 C g −1 at current density of 10 mA cm −2 for 1 h. Solar energy was integrated with electrochemical reactor for the regeneration of adsorbent to make the system cost‐effective and self‐sustainable. Practitioner points: Industrial hazardous wastewater treatment with a cost‐effective graphite integrated adsorbent. Development of renewable solar energy‐integrated with electrochemical system for regeneration. Regeneration efficiency of adsorbent Nyex™ 1000 was achieved around 99.5% with integrated system. Sustainable system was introduced to incorporate with renewable energy for waste water treatment. Abstract : Hazardous industrial wastewater using cost‐effective graphite adsorbent along with electrochemical regeneration integrated with renewable solar energy was used to treat effluent containing crystal violet dye. Cost‐effective graphite adsorbent has a surface area of 1.0 m 2  g −1 . The solute removal efficiency was found more than 90%.